COVID-19 PANDEMIC HANDLING STRATEGIES BY THE BADUY TRIBE - Irmayanto, Randi; Darmawan, Ede Surya (UI Scholars Hub, 2022)
The first case of COVID-19 in Indonesia was announced by the President on March 2, 2020. As of June 22, 2022, the cumulative number of confirmed positive cases in Indonesia is 6,072,918 cases, with 5,904,825 recoveries and 156,702 deaths. In response to this case, the government made a policy starting with Large-Scale Social Restrictions contained in Government Regulation Number 21 of 2020 until the Enforcement of Restrictions on Community Activities based on levels (4, 3, 2, and 1) set by the Ministry of Home Affairs. The government's strategy to deal with this is through the 5M health protocol (wearing masks, washing hands, maintaining distance, staying away from crowds, and reducing mobility), 3T (testing, tracing, treatment), and vaccinating. In this regard, an interesting condition occurs in the Baduy tribe in Kanekes Village, Lebak Regency, Banten. The Cisimeut Health Center which oversees the Kanekes Village area noted that so far there have been no reports of positive cases in the village. The results of the PRA (Participatory Rural Appraisal) and document review show that the combination of traditional strategies and modern strategies in accordance with government policies is carried out in the Baduy Tribe. The obedience of the Pu'un (Chief of the Tribe) to the government is an important factor in the success of this strategy.